2010
DOI: 10.1007/s10964-010-9608-4
|View full text |Cite
|
Sign up to set email alerts
|

Who is Likely to Help and Hurt? Profiles of African American Adolescents with Prosocial and Aggressive Behavior

Abstract: Prosocial behavior and aggression among children and adolescents are important indicators of social and interpersonal competence. The goal of this study was to investigate whether there are different prototypes among African American adolescents that can help explain prosocial and aggressive (relational and overt) behaviors. Also of interest was whether these profiles differed for boys and girls. The selection of independent variables (e.g., empathy, anger management, normative beliefs about aggression, and et… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 67 publications
2
36
0
3
Order By: Relevance
“…This refers to the importance of emotional expressiveness and of being in tune with the feelings and emotional needs of others . Research with African Americans has shown that affect sensitivity is a predictor of empathy, a factor associated with prosocial behavior . The protective effects of emotional expressiveness on physical and mental health outcomes has also been documented .…”
Section: Cultural Considerationsmentioning
confidence: 99%
“…This refers to the importance of emotional expressiveness and of being in tune with the feelings and emotional needs of others . Research with African Americans has shown that affect sensitivity is a predictor of empathy, a factor associated with prosocial behavior . The protective effects of emotional expressiveness on physical and mental health outcomes has also been documented .…”
Section: Cultural Considerationsmentioning
confidence: 99%
“…Altruistic prosocial behavior was associated with significantly lower reports of antisocial behavior. This is in line with previous work examining prosocial behavior as a more general construct (Allen & Philliber, ; Belgrave et al., ; McMahon et al., ). Prosocial behavior has been consistently associated with a reduction in negative outcomes in predominately White American adolescents; the current study provides evidence that such behaviors are also protective for African American youth.…”
Section: Discussionmentioning
confidence: 99%
“…That is, clinicians and educators should take into account the cultural background of aggressive adolescents. To enhance positive outcomes, future interventions to prevent aggression should link youth to their ethnic identity to foster feelings of commitment and pride (Belgrave et al, 2011).…”
Section: Discussionmentioning
confidence: 99%